Hot Ductility and Fracture Behavior of High‐Ti Weathering Steel. Issue 6 (5th March 2021) - Song, Li-Ying; Gao, Xiu-Hua; Xue, Qi-He; Sun, Chao; Wang, Ming-Ming; Devesh Kumar Misra, R.; Zhang, Xiao-Lei; Wu, Hong-Yan; Du, Lin-Xiu
Abstract : The hot ductility behavior of high‐Ti weathering steel is studied by high‐temperature tensile testing in the temperature range of 650–1100 ºC. The results reveal a ductility trough in high‐Ti steel in the range of 650–962, 650–925, and 700–880 °C with minimum reduction in area (RA) of 22.21%, 36.53%, and 43.25% at 800 ºC and different strain rates of 1.0 × 10 −3, 5.0 × 10 −3, and 1.0 × 10 −2 s −1, respectively. A number of secondary cracks containing S, N, and Ti propagate along the grain boundary, and the obvious preferred orientation is found in the microstructure near the fracture at 800 °C. With the increase in strain rate, the value of RA is increased in the temperature range of 650–1050 ºC, such that the probability of crack occurrence is decreased. RA does not increase with the increase in strain rate at 1100 °C and strain rate of 1.0 × 10 −2 s −1 . The underlying reason is that there is not adequate time for the material to recover or recrystallize with the increase in strain rate, resulting in material softening effect that is not completely reflected. Abstract : The reduction in area (RA) of high‐Ti weathering steel reaches the minimum at 800 °C. The mechanism is that a layer of proeutectoid ferrite can be formed along austenite grain boundaries at the top part of the ferrite–austenite region, making the grain boundary area weakened. The hot ductility of steel gradually recovers with the ferrite thickening.